Analisis Manajemen Resiko Dalam Penerapan Good Corporate Governance : Studi pada Perusahaan Perbankan di Indonesia - Maya Sari; Seprida Hanum; Rahmayati Rahmayati (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to analyze risk management in the implementation of good corporate governance in banking companies in Indonesia. This research was conducted on the Indonesia Stock Exchange (IDX), especially for banking sector companies which are available on the official website www.idx.co.id. This study uses a quantitative descriptive research approach. In this study, the authors collect research data and information using the documentation process by collecting instruments related to risk management and good governance. In this study, the data analysis technique used is descriptive analysis which is defined as a method of data analysis by describing, describing, and describing the subject or object under study based on the facts that are seen or what they are. The results show that the application of the concepts and principles of Good Corporate Governance in risk management involves banking internal organs. All internal banking elements such as shareholders, GMS forums, commissioners, directors, management of the audit committee, internal and external auditors as well as employees must be able to form a circle and work situation that supports each other and plays an active role in implementing the principles of Good Corporate Governance, especially in dealing with and manage various types of risks that specifically have their own uniqueness that only exists in banking.